Documents pertaining to the St. Francis/Sokoki Band of Abenakis of Vermont Petition for Federal Acknowledgment as an Indian Tribe - United States. Bureau of Indian Affairs; Vermont. Office of the Attorney General (2002)
Much of this material consists of historical materials, including printed and archival sources from multiple institutions, including the APS, regarding Abenaki people and history, assembled by the State of Vermont's Office of the Attorney General in relation to the St. Francis/Sokoki Band of Abenakis of Vermont Petition for Federal Acknowledgment as an Indian Tribe.